Practical Ext JS projects with Gears - Zammetti, Frank W.; Safari eBooks (Berkeley, Calif. : Apress ; New York : Distributed to the book trade worldwide by Springer-Verlag New York, 2009)
"Using a pragmatic approach to learning all about Ext JS, you'll dissect seven full-fledged applications and realize the potential of Ext JS in modern RIA development"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Web site development -- Computer programs; Ajax (Web site development technology); JavaScript (Computer program language); Electronic books